Sustainability principles and practice - Robertson, Margaret (Routledge; New York, 2014)
"Sustainability: Principles and Practice gives an accessible and comprehensive overview of the interdisciplinary field of sustainability. The focus is on furnishing solutions and equipping the student with both conceptual understanding and technical skills for the workplace. Each chapter explores one aspect of the field, first introducing relevant theory and presenting issues, then supplying tools for working toward solutions. Elements of sustainability are examined piece by piece, and wide coverage ranges over ecosystems, social equity, environmental justice, food, energy, product life cycles, cities, and more. Techniques for management and measurement as well as case studies from around the world are provided. Chapters include further reading, discussion questions, and problems to foster quantitative thinking. The book is supported by a companion website with key website links, detailed reading lists, glossary, and additional case studies, together with numerous projects, research problems, and group activities, all of which focus on real-world problem solving of sustainability issues.The textbook is designed to be used by undergraduate college and university students in sustainability degree programs and other programs in which sustainability is taught. "--
"Sustainability: Principles and Practice gives an accessible and comprehensive overview of the interdisciplinary field of sustainability, equipping the student with both conceptual understanding and technical skills for the workplace. Each chapter presents jointly issues and solutions, which range from ecosystems, social equity and environmental justice to food, growth, consumption and cities, along with a discussion of techniques for management and measurement. The textbook introduces relevant theory at the beginning of each chapter as well as providing a wealth of international case studies, including policies on waste, energy, water, buildings, and greenhouse gas emissions in the US and the European Union and examples from the China, Sweden, Singapore, Eastern Europe, Central Asia and Africa"--
Includes bibliographical references and index.
Keywords: Sustainability -- Textbooks; Sustainable development -- Textbooks; Environmental economics -- Textbooks; Business & economics / Development / Economic Development; Business & economics / Development / Sustainable Development; BUSINESS & ECONOMICS / Environmental Economics